(NpRAKTI^ESKAQ METODIKA PREPODAWANIQ RUSSKOGO QZYKA NA NA^ALXNOM \TAPE (B:s (P(NUSSKIJ QZYK KAK INOSTRANNYJ(B) /s - (NaLEKSEEWA(B, (NnATALIQ nIKOLAEWNAs; (NbARABANOWA(B, (Nn(B.(Nr(B.s ((NmOSKWA (B:s (NrUS(B. (NQZ(B.,s, 1990)
(NbIBLIOGR(B.: (NS(B. 220 - 228s
Keywords: (NmETODIKA PREPODAWANIQ NERUSSKIMs; (NrUSSKIJ QZYK DLQ INOSTRANCEWs